Parents’ influence on children’s online usage - Yusuf, Sarina; Osman, Mohd. Nizam; Hassan, Md. Salleh; Teimoury, Misha (Elsevier (ScienceDirect), 2014)
Children nowadays has unlimited access to the Internet that possibly will harm them, thus parents’ roles in mitigating their children online risks is crucial. Previous studies show a positive parent-child attachment may reduce the risks. A survey was conducted and a total of 387 participants aged 9 to 16 have been recruited to completed a 14-item questionnaire form. The instrument consists of three sub-scales, namely trust, communication and alienation. Results showed that almost 80% of children in this study trust their parents, feel their parents’ concern (75%), and depend on their parents (74%). Malaysian children are actually very in need to be safe during online due the facts that they knew regarding the Internet effects. They also show a willingness to do the right things by letting their parents involve into their online live activities.